IMPLICATION OF WEST LOMBOK REGULATION NO. 20 YEAR 2021 CONCERNING VILLAGE CHIEF ELECTION ON THE RIGHT TO VOTE AND BE ELECTED - Fauzi sariani; Agus Dedi Putrawan (Politea : Jurnal Politik Islam, 2021)
Based on the principle of regional autonomy and the task of assisting the regions, they are given autonomous rights to regulate and manage their own households. Apart from that, regions are also given the right to make regulations that are in accordance with the needs of the region. The constitution must be contained in all types of regulations, both in the form of laws and regional regulations, so if they are not in accordance with these principles, the regulation can be canceled or null and void. West Lombok Regency has issued Regent Regulation No 20 of 2021 concerning the village Chief election with the delegation of authority from domestic government regulations 112 of 2014 concerning Village Chief Elections to further regulate in accordance with the conditions of the society in the area, in article 21 paragraph (2) of the Minister of Home Affairs Regulation in stipulates the candidate's requirements, namely "Be fearful of God Almighty" then added to regent regulation of the West Lombok in article 24 Paragraph (2) to "Be cautious of God Almighty and be able to read their respective holy books" but in the implementation stage, the regent regulation field this resulted in conflicts both occurring between the village chief election committee and the candidate for the village chief as well as with the community its self, as happened in Jembatan Kembar Timur Village, Lembar District, West Lombok and Taman Baru Village, Sekotong District, West Lombok.